Acknowledgement to Reviewers of Dentistry Journal in 2016 - Dentistry Journal Editorial Office (MDPI AG, 2017)
The editors of Dentistry Journal would like to express their sincere gratitude to the following reviewers for assessing manuscripts in 2016.[...]